Effet de la fumure en potassium sur le developpement, la survie et la fecondite de Sesamia calamistis Hampson (Lepidoptera: Noctuidae) et de Eldana saccharina Walker (Lepidoptera: Pyralidae) - Denké, K.; Schulthess, F.; Bonato, O.; Gounou, S.; Smith, J. (Springer, 2000)
The effect of potassium application to maize plants on the development, survival and fecundity as well as larval and pupal weight of Sesamia calamistis and Eldana saccharina were studied in the laboratory. Six different potassium treatments corresponding to 0, 30, 60, 60, 90, 120 and 150 kg K2O/ha were used. Potassium had no influence on larval and pupal developmental time or longevity of adult S. calamistis. The highest larval mortality was observed at 0 and at 150 kg K2O/ha. Increased doses (> 60 kg K2O/ha.) tended to reduce pupal survival. The lowest pupal weight was obtained at 150 kg/ha whereas fecundity was negatively related with potassium. The highest values of intrinsic rate of increase (rm) and net reproductive rate (Ro) were obtained with 60 kg K2O/ha and lowest with 150 kg K2O/ha. For E. saccharina, potassium had no significant effect on larval and pupal developmental time, larval survival, and pupal weight. The highest larval weight, pupal survival and fecundity as well as rm and Ro values were observed at 90 kg K2O/ha.